Need of A Global Aviation Standard Compliance? Air Passenger Rights in Indonesia and Madagascar - Prabandari, Adya Paramita; Manitra, Ramalina Ranaivo Mikea (Jurnal Hukum IUS QUIA IUSTUM, 2025)
Air passenger right is a crucial aspect of modern aviation law, ensuring the protection of passengers and promoting accountability among air carriers. This research examines the legal framework governing air passenger rights in Indonesia and Madagascar, comparing them to international standards such as the Montreal Convention of 1999 and Core Principles on Consumer Protections of ICAO and IATA. The research method is comparative law method, complemented with normative and conceptual approaches, using secondary data analysed qualitatively to obtain a deductive analysis. While both countries have regulations protecting passenger interests and outlining carrier obligations, Indonesia demonstrates stronger compliance, particularly in compensation provisions and enforcement mechanisms, whereas Madagascar lacks fixed compensation rules and explicit protections for passengers with disabilities. Through a detailed analysis of relevant laws and regulations, this research highlights where national laws fall short of global norms, emphasising the need for greater alignment with international standards to ensure consistency and accountability in air travel. Recommendations include revising Madagascar’s legal framework to introduce fixed compensation rules, establish clear complaint-handling procedures, and incorporate explicit protections for passengers with disabilities. For both countries, strengthening enforcement mechanisms and adopting mandatory insurance requirements would improve passenger protection, legal certainty, and alignment with international standards.Keywords: Air Passenger Rights, Indonesia, International Air Law, Madagascar AbstrakHak penumpang pesawat merupakan aspek penting dari hukum penerbangan kontemporer, yang menjamin perlindungan penumpang dan mendorong akuntabilitas maskapai penerbangan. Penelitian ini mengkaji kerangka hukum nasional yang mengatur hak penumpang pesawat yang berlaku di Indonesia dan Madagaskar, dan membandingkannya dengan standar internasional seperti Konvensi Montreal tahun 1999 dan Prinsip Utama tentang Perlindungan Konsumen ICAO dan IATA. Metode penelitian yang digunakan adalah metode hukum komparatif, dilengkapi dengan pendekatan normatif dan konseptual, menggunakan data sekunder yang dianalisis secara kualitatif untuk memperoleh analisis deduktif. Meskipun kedua negara memiliki peraturan yang melindungi kepentingan penumpang dan menguraikan kewajiban maskapai, Indonesia di satu sisi, menunjukkan kepatuhan yang lebih kuat, khususnya dalam ketentuan kompensasi dan mekanisme penegakan hukum; sedangkan Madagaskar di sisi lain tidak memiliki aturan kompensasi tetap dan perlindungan eksplisit bagi penumpang penyandang disabilitas. Melalui analisis terperinci terhadap undang-undang dan peraturan yang relevan, penelitian ini menyoroti di mana undang-undang nasional tidak memenuhi norma global, yang menekankan perlunya penyelarasan yang lebih baik dengan standar internasional untuk memastikan konsistensi dan akuntabilitas dalam perjalanan udara. Rekomendasi yang diberikan meliputi revisi kerangka hukum Madagaskar untuk memperkenalkan aturan kompensasi tetap, menetapkan prosedur penanganan pengaduan yang jelas, dan memasukkan perlindungan eksplisit bagi penumpang penyandang disabilitas. Bagi kedua negara, penguatan mekanisme penegakan hukum dan penerapan persyaratan asuransi wajib akan meningkatkan perlindungan penumpang, kepastian hukum, dan keselarasan dengan standar internasional.Kata Kunci: Hak Penumpang Udara, Indonesia, Hukum Udara Internasional, Madagaskar